2020
DOI: 10.1080/21623945.2020.1721692
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Gla protein regulates adipogenesis and is serum marker of visceral adiposity

Abstract: Objective Matrix Gla protein (MGP) is a potent calcification inhibitor. Mgp-/mice display increased proportion of brown adipose tissue. However, whether MGP is involved in fat metabolism remains unclear. This study aims to investigate the involvement. Methods Expression of adipocyte differentiation markers was examined by RT-qPCR. Adipocyte formation was assessed by Oil Red staining. Serum triglyceride, cholesterol, and desphosphorylated-uncarboxylated MGP (dp-ucMGP) were quantified by ELISA. Visceral fat was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
(42 reference statements)
1
25
0
1
Order By: Relevance
“…Obesity is linked with vitamin K deficiency [ 167 , 168 , 169 ]. Vitamin K deficiency results in decreased vitamin K-dependent carboxylation and phosphorylation of Gla-proteins and, as a consequence, into elevated levels of circulating desphosphorylated-uncarboxylated matrix Gla protein (dp-ucMGP).…”
Section: Underlying Mechanisms Linking Obesity To Major Complications As a Results Of Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is linked with vitamin K deficiency [ 167 , 168 , 169 ]. Vitamin K deficiency results in decreased vitamin K-dependent carboxylation and phosphorylation of Gla-proteins and, as a consequence, into elevated levels of circulating desphosphorylated-uncarboxylated matrix Gla protein (dp-ucMGP).…”
Section: Underlying Mechanisms Linking Obesity To Major Complications As a Results Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Recent research studied the relationship between obesity and serum dp-ucMGP in a cohort of 278 Chinese Han people. The results demonstrated that serum dp-ucMGP level was positively associated with visceral fat index, waist height ratio, but not BMI [ 167 ]. In addition, lower vitamin K2 levels were observed in obese hemodialysis patients compared to non-obese patients [ 168 ].…”
Section: Underlying Mechanisms Linking Obesity To Major Complications As a Results Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…The resulting transcriptome represented the early response elements that potentially initiated MSC's early lineage commitment as a result of the on-cell-tethered biomaterial's mechanical properties. Notably, cells tethered in soft microgels were enriched in expression of pro-adipogenic factors including LGALS1, [37] MGP, [38] ADIRF, [39] and COX7A1, [40] while cells tethered in stiff microgels expressed more pro-osteogenic factors such as FOSB, [41] STC1, [42] BMP2, and BMP6. [43] Gene ontology (GO) enrichment analysis of the differentially expressed genes suggested that early stem cell commitment associates at the genetic level with altered TGFB/SMAD signaling and metabolic (i.e., mitochondrial) behavior (Figure 3j,k; Tables S5 and S6, Supporting Information).…”
Section: Temporal Stiffening Of Tethered Biomaterials Controls Early Onset Stem Cell Lineage Commitmentmentioning
confidence: 99%
“…26 ). Furthermore, these genes were reported to be higher expressed in visceral compared to subcutaneous ASPCs and have as such been associated with the impaired capacity of visceral ASPCs to give rise to in vitro adipocytes (Reichert et al , 2011; Meissburger et al , 2016; Takeda et al , 2016; Li et al , 2020). Further studies will now be required to investigate how this seemingly diverse collection of molecules may cooperate within the retinoic acid signalling pathway to steer the developmental, phenotypic and functional properties of Aregs.…”
Section: Discussionmentioning
confidence: 99%